Tertiary Education, Investment, and Labor Force Participation as Determinants of Indonesia’s Economic Growth: Evidence from ARDL Analysis, 1990–2023 - Anisa, Aan; Kenedi, Kenedi; Agustini, Anti Wulan (Forum Kerjasama Pendidikan Tinggi, 2025)
The relationship between higher education and economic growth has been widely discussed, yet evidence from emerging economies such as Indonesia remains inconclusive, particularly when considering the interplay of education, investment, and labor market dynamics. This study seeks to address this gap by analyzing Indonesia’s economic performance from 1990 to 2023 using annual time-series data sourced from the World Bank. Employing the Autoregressive Distributed Lag (ARDL) approach, the analysis reveals that tertiary education enrollment exerts a significant positive contribution to economic expansion (coefficient = 0.0118, p < 0.01), while investment demonstrates a robust growth-enhancing effect (coefficient = 0.3859, p < 0.01). By contrast, labor force participation shows a negative association (coefficient = –0.0164, p < 0.05), reflecting structural inefficiencies in the labor market. In the short horizon, investment delivers immediate and significant benefits (coefficient = 0.4016, p < 0.01), whereas changes in labor force participation appear statistically negligible. The error correction term (–0.4622, p < 0.01) further indicates a moderate pace of adjustment, with nearly 46% of disequilibria resolved annually. These results highlight the need for policies that strengthen higher education quality, sustain a favorable investment climate, and reform labor markets, thereby ensuring that Indonesia moves toward inclusive and sustainable development.